Implementasi Malware Security and Proxy Layer 7 Protocol at Routerboard Mikrotik - Intan Kumalasari; Aswin Yadi Saputra (Komunitas Dosen Indonesia, 2022)
In today's era along with the times, the internet network is needed in finding information because the internet is used as a source of information and exchange data in real time. Therefore, the internet is used in daily human activities, especially in the world of education. In the world of education, the internet is used as a means of online learning and as a source for finding learning materials related to education. In an educational institution, the number of users connected to the internet network is very large, making it possible for infiltration by malware and distribution. Malware activity is closely related to computer memory, computer performance and also network activity on computer systems making it difficult to access learning media sites in the network because there is no network security management that regulates the data exchange traffic of each user. The right solution to overcome this problem is to implement malware security and proxy server configurations as the method used to manage traffic for data exchange activities. The methodology used is dynamic analysis by analyzing malware on a system and looking at the activities or processes activated by the malware. By applying the security malware method and proxy server configuration, the quality of the network will be better because it minimizes malware traffic on the network system according to the configuration that is applied and also users will be restricted from accessing certain sites.